DNA aptamers that target human glioblastoma multiforme cells overexpressing epidermal growth factor receptor variant III in vitro - Tan Yan; Shi Yu-sheng; Wu Xi-dong; Liang Hui-yu; Gao Yu-bo; Li Shu-ji; Zhang Xing-mei; Wang Fang; Gao Tian-ming (Acta Pharmacologica Sinica, 2016)
Aim: Aptamers are oligonucleic acid or peptide molecules that bind to a specific target molecule in cells, thus may act as effective vehicles for drug or siRNA delivery. In this study we investigated the DNA aptamers that target human glioblastoma multiforme (GBM) cells overexpressing epidermal growth factor receptor variant III (EGFRvIII), which was linked to radiation and chemotherapeutic resistance of this most aggressive brain tumor. Methods: A 73-mer ssDNA library containing molecules with 30 nt of random sequence flanked by two primer hybridization sites was chosen as the initial library. Cell systematic evolution of ligands by exponential enrichment (Cell-SELEX) method was used to select the DNA aptamers that target EGFRvIII. The binding affinity of the aptamers was measured using a cell-based biotin-avidin ELISA. Results: After 14 rounds of selection, four DNA aptamers (32, 41, 43, and 47) that specifically bound to the EGFRvIII-overexpressing human glioma U87Δ cells with Kd values of less than 100 nmol/L were discovered. These aptamers were able to distinguish the U87Δ cells from the negative control human glioma U87MG cells and HEK293 cells. Aptamer 32 specifically bound to the EGFRvIII protein with an affinity similar to the EGFR antibody (Kd values of aptamer 32 and the EGFR antibody were 0.62±0.04 and 0.32±0.01 nmol/L, respectively), and this aptamer was localized in the cell nucleus. Conclusion: The DNA aptamers are promising molecular probes for the diagnosis and treatment of GBM.